Clonidine as an adjuvant to ropivacaine-induced supraclavicular brachial plexus block for upper limb surgeries - Kalyani Nilesh Patil; Noopur Dasmit Singh (Wolters Kluwer Medknow Publications, 2015)
Background and Aims: Ropivacaine is a new amide, long acting, pure S-enantiomer, local anesthetic, with differential blocking effect. The addition of clonidine to local anesthetic improves the quality of peripheral nerve blocks. This study was conducted to evaluate the effect of clonidine on characteristics of ropivacaine-induced supraclavicular brachial plexus block. Material and Methods: A total of 60 adult patients were randomly recruited to two groups of 30 each: Group I: 30 ml 0.75% ropivacaine + 1 ml normal saline. Group II: 30 ml 0.75% ropivacaine + 1 mcg/kg clonidine diluted to 1 ml with normal saline. Results: The onset of sensorimotor block was earlier in Group II (4.36 ± 0.81 min for sensory block and 9.83 ± 1.12 min for motor block) than in Group I (4.84 ± 0.65 min for sensory block and 10.85 ± 0.79 min for motor block). The duration of both sensory and motor block were significantly prolonged by clonidine (P < 0.001). The duration of analgesia was also prolonged in patients receiving clonidine (613.10 ± 51.797 min vs. 878.33 ± 89.955 min). Although incidence of hypotension and bradycardia was higher in Group II when compared to Group I, it was not clinically significant. Conclusions: Ropivacaine 0.75% is well-tolerated and provides effective surgical anesthesia as well as relief of postoperative pain. Clonidine as an adjuvant to ropivacaine significantly enhances the quality of supraclavicular brachial plexus block by faster onset, prolonged duration of sensory and motor block and improved postoperative analgesia, without associated adverse effects at the dose used.